The role of selenium intervention in gut microbiota homeostasis and gene function in mice with breast cancer on a high-fat diet - Li, Yinan; Liu, Min; Kong, Bingtan; Zhang, Ganlin; Zhang, Qing (Frontiers in Microbiology, 2024)
Objective: This study aimed to investigate the effect of selenium on gut microbiota in mice with breast cancer under a high-fat diet.Methods: Twelve female BALB/c mice were randomly divided into two groups: 4T1+selenium+ high-fat diet group and 4T1+high-fat diet group. Mice were injected with 4T1 cells on the right 4th mammary fat pad and kept on a high-fat diet. Fecal samples were collected, and DNA was extracted for metagenomics sequencing and bioinformatics analysis. Relevant target genes and pathways were annotated and metabolically analyzed to explore the intervention effect of selenium on breast cancer in the high-fat diet state.Results: Selenium supplementation in the high-fat diet altered the composition and diversity of gut microbiota in mice with breast cancer. The gut microbial composition was significantly different in the selenium intervention group, with increased abundance of Proteobacteria, Actinobacteria, Verrucomicrobia phylum, and species like Helicobacter_ganmani, Helicobacter_japonicus, and Akkermansia_muciniphila, while phyla like Bacteroidetes, Firmicutes, Deferribacteres, Spirochaetes, and species like Prevotella_sp_MGM2, Muribaculum_intestinale, Lactobacillus_murinus, and Prevotella_sp_MGM1 were decreased. Functional analysis revealed differential expression of genes related to carbohydrate active enzymes, pathogen-host interactions, cell communication, cell auto-induction, membrane transporters, and virulence factors. Furthermore, 37 COGs and 48 metabolites with rising metabolic potential in the selenium intervention group were predicted.Conclusions: Selenium alters the homeostasis of gut microbiota in mice with breast cancer on a highfat diet, affecting their composition, abundance, and associated metabolism. These findings suggest that the mechanism involves interfering with gut microbiota homeostasis, leading to altered synthesis of tumor-associated proteins and fatty acids and inducing tumor cell apoptosis and pyroptosis.